The Interactive Design of Library Information Sharing in View of Network Communication Technology. (19th March 2022) - Zhen, Yeping
Abstract : From the perspective of data viewing, interactive design is to present abstract information and data in a visual form through a computer interface. It is formulated based on a humanized and flexible human-computer interaction model. The interaction process between computers and humans requires careful thinking and design. It must follow the principle of "user first, machine second." Understanding the audience's psychology and behavior characteristics can effectively enhance computer vision interaction and expand the scope of the audience. The research in this study aimed at the interactive design of library information sharing based on network communication technology. It introduces the organizational structure of the library and analyzes in detail the problems that the current library information resource sharing still faces. Then, this study proposes a dynamic differentiated service mechanism of DDSM to improve the success rate of information transmission in the interactive design system. This study designs an experiment on the interactive design of library information sharing by multiple types of users. The results of the experiment show that students of all grades and teachers use the library and library websites more frequently. For the interactive information service of the library, users are most satisfied with the project attitude of the book recommendation service method. Its satisfaction rate reaches 68%, and it is also the most popular among users. The main purpose of the interaction between library users is to share knowledge. However, the current domestic academic libraries have a general sense of interactive information services, and the development speed has always been slower than that in foreign countries.